2003
DOI: 10.1086/378657
|View full text |Cite
|
Sign up to set email alerts
|

Complex Transitions between C3 and C4 Photosynthesis during the Evolution of Paniceae: A Phylogenetic Case Study Emphasizing the Position of Steinchisma hians (Poaceae), a C3‐C4 Intermediate

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to International Journal of Plant Sciences.A two-tiered, nested molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Sequence determination followed standard methods (Clark et al 1995;Duvall and Morton 1996). GenBank accession numbers for the complete set of sequences analyzed, together with voucher specimen information for newly determined sequences, are provided in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence determination followed standard methods (Clark et al 1995;Duvall and Morton 1996). GenBank accession numbers for the complete set of sequences analyzed, together with voucher specimen information for newly determined sequences, are provided in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent phylogenetic study of another plastid locus, the rpoC2 insert, Micrairoideae, represented by Eriachne ALISO Duvall, Davis, Clark, Noll, Goldman, and Sánchez-Ken mucronata R. Br., Isachne distichophylla G. C. Munro ex Hillebr., and Pheidochloa gracilis S. T. Blake, were similarly resolved as monophyletic (Duvall et al 2003). The position of Micrairoideae among the PACMAD subclades was unresolved in MP (Fig.…”
Section: Micrairoideaementioning
confidence: 95%
See 1 more Smart Citation
“…Both the distribution of C 4 grasses in distinct taxonomic groups and the high variability of their C 4 syndrome led to the inference of multiple origins of the C 4 pathway in this family (Sinha and Kellogg, 1996;Kellogg, 2001). Phylogenetic analyses of the subfamily Panicoideae further suggested that C 4 photosynthesis appeared several times independently, although a single appearance followed by multiple reversions could not be excluded (Giussani et al, 2001;Duvall et al, 2003;Vicentini et al, 2008). The ancestral state reconstructions adopted in these studies are strongly dependent on species sampling and rely on statistical methods whose assumptions can produce different results.…”
Section: Evolutionary Lineages In Grassesmentioning
confidence: 99%
“…Phylogenetic studies, based on morphological and molecular characters, have firmly demonstrated that Panicum in its traditional sense is not monophyletic (Gómez-Martínez and Culham 2000;Zuloaga et al 2000;Duvall et al 2001Duvall et al , 2003Giussani et al 2001;Aliscioni et al 2003). These studies allowed new delimitations within the Paniceae, such as the recognition of four genera, previously treated by Zuloaga (1987) at subgeneric level: Dichanthelium (Hitchc.…”
Section: Introductionmentioning
confidence: 99%